Super-ovulatory response of pregnant mare serum gonadotropin (PMSG) treatment on ovarian characteristics of rabbit does under heat stress - RHOUMA, RAOUIA BEN; AROUA, MOHAMED; M’HAMDI, NACEUR (The Indian Journal of Animal Sciences, 2022)
The main aim of this study was to determine the effects of superovulation treatment on ovarian characteristics, follicle and embryo number of rabbit does under heat stress. Fourty-eight hours before natural mating, 30 rabbits were divided into three equal groups, viz. control (G1) were injected with 0.1 ml saline/doe and two treatment groups (G2, G3) were injected with 20 IU and 40 IU of pregnant mare serum Gonadotropin (PMSG). After 72 h of natural mating, does in all groups were slaughtered. The genital tract measurement was taken, the embryos were morphologically evaluated, and oocytes and follicle count were recorded. No significant effect of PMSG on ovarian measurement was observed. For corpora lutea number and embryo number from the oviduct and uterine horn, there were no significant effects of PMSG in all the groups.